Type Ia Supernovae as Probes of the Interstellar Medium in Galaxies. Issue Volume 9:Issue S297(2013) (21st February 2014) - Cox, N. L. J.; Patat, F.
Abstract: We present and discuss recent results from observations of bright Type Ia supernovae as probes of physical and chemical condtions of extra-galactic interstellar clouds. To illustrate the case we present new results obtained for SN 2009ig.